Analisis Kegiatan-Kegiatan Seremonial Formal di SMPN 5 Jember Kaitannya dengan Prestasi Sekolah - Bahiroh, Siti Nur; Wildan, Thoriq; Sarwono, Syazwina Ramaita Awra; Isnyna, Zahro Shabina; Mahardika, I Ketut (Jurnal Ilmiah Wahana Pendidikan, 2024)
This journal analyzes formal ceremonial activities carried out at SMPN 5 Jember with school achievements. This research was conducted with the aim of finding out the relationship between formal ceremonial activities and school achievement. The research method used is a qualitative research method that uses interview observation data collection techniques, which include observation of activities and direct interactions with students, teachers and school staff who are involved in environmental care activities. The results of the research show that formal ceremonial activities at SMPN 5 Jember are related to school achievement, one of which is the Adiwiyata school award throughout Jember Regency. This can be seen from the high level of participation of students and teachers in the environmental care program, as well as an increase in student motivation and learning habits after implementing these activities. Based on this analysis, it is recommended that other schools also implement environmentally caring habits that can improve school achievement and environmental sustainability